'No one was there to care for us': Ashodaya Samithi's community-led care and support for people living with HIV in Mysore, India. Issue 4 (20th April 2016) - Chevrier, Claudyne; Khan, Shamshad; Reza-Paul, Sushena; Lorway, Robert
ABSTRACT: Under the umbrella of the Bill and Melinda Gates-funded HIV initiative in India, the Mysore-based sex workers' (SWs) collective Ashodaya Samithi focused on improving its members' living and working conditions through community-led structural interventions, including community mobilisation, advocacy, peer-led support, and health promotional activities. Based on four months of ethnographic fieldwork, this article examines the care and support activities of one of its sub-wings, Ashraya, which specifically focuses on people living with HIV and AIDS (PLHIV). We first discuss the stigma-related perceptions and experiences of participants in relation to health-care settings and work environment, families and communities, and within varied HIV support networks. We then explore how Ashraya's community-led interventions attempt to challenge the structural forces feeding on and creating stigma. We argue that the current policy focus on the involvement of SWs' collectives in sexually transmitted infection (STI) prevention in India is rather limited and should be expanded along the continuum of care and support offered to PLHIV. As suggested in this paper, SWs' organisations may have greater potential to contribute to more than STI prevention work, both within and outside their communities, than currently recognised.